2009
DOI: 10.1521/bumc.2009.73.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties and validity of the Dutch Inventory of Personality Organization (IPO-NL)

Abstract: This study investigated the psychometric qualities and validity of a Dutch translation of the Inventory of Personality Organization (IPO-NL) in a heterogeneous sample of 371 psychiatric patients and a sample of 181 normal controls. Results show good internal consistency and test-retest reliability. Exploratory factor analyses did not replicate its proposed five-factor structure, but suggested a four-factor structure instead. The IPO-NL appeared to have good concurrent validity across populations, and good conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
49
0
11

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 17 publications
6
49
0
11
Order By: Relevance
“…Studies need to examine the dimensions or components comprising PO. For instance, studies on multiple measures of PO have failed to find evidence for a neat distinction between identity diffusion and primitive defenses (Berghuis, Kamphuis, Boedijn, & Verheul, 2009;Gamache et al, 2009;Smits et al, 2009). Similarly, multilevel techniques could help elucidate the interrelationships between basic components of PO, and thus examine which specific indices of level of PO (e.g., object relations) determine which particular manifestations of PO (e.g., Laverdière et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Studies need to examine the dimensions or components comprising PO. For instance, studies on multiple measures of PO have failed to find evidence for a neat distinction between identity diffusion and primitive defenses (Berghuis, Kamphuis, Boedijn, & Verheul, 2009;Gamache et al, 2009;Smits et al, 2009). Similarly, multilevel techniques could help elucidate the interrelationships between basic components of PO, and thus examine which specific indices of level of PO (e.g., object relations) determine which particular manifestations of PO (e.g., Laverdière et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no one has investigated the properties of the SCL-90-R with respect to PDs. This should be an important topic because the SCL-90-R is among the most frequently used questionnaires in clinical practice, and most of all because it seems to be an increasing tendency to implement the PSI among other clinical measures (Berghuis, Kamphuis, Boedijn, & Verheul, 2009;Meurle-Hallberg & Armelius, 2006;Narud, Mykletun & Dahl, 2005). According to the studies of Karterud et al (1995) and Starcevic et al (2000), clinicians can make some inferences regarding personality pathology by investigating an SCL-90-R profi le.…”
Section: Introductionmentioning
confidence: 99%
“…Lower scores on this factor should be related to neurotic personality organization. The second factor (reality testing) was composed of almost alloriginal reality testing items, supporting the structural integrity of the original subscale (Berghuis et al, 2009). This factor differentiates a psychotic personality organization from a neurotic and borderline personality organization, because individuals with a psychotic personality organization show, in addition to severe identity diffusion and primitive defenses, a loss of reality testing.…”
Section: Introductionmentioning
confidence: 67%
“…The original IPO has five subscales: reality testing, defense mechanisms, identity diffusion, aggression and moral values. Various recent factor analytical studies however did not replicate its proposed five‐factor structure but suggested a four‐factor structure instead: general personality pathology, reality testing, aggression and sadistic aggression (for instance, Berghuis, Kamphuis, Boedijn, & Verheul, ). According to Berghuis et al (), the first factor reflects general personality pathology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation